Analisis Pengaruh Jumlah Penduduk Terhadap Kemiskinan Melalui Pendapatan Per Kapita Sebagai Variabel Mediasi - Ali Asdon Tanjung; Dafa Ariza; Feryanto Nababan; Raymond Panuturi Siboro; Zaki Edi Saputra; Armin Rahmansyah Nasution; Nasrullah Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of population on poverty with per capita income as a mediating variable in Aceh Province, a special autonomy region that still faces structural poverty challenges post-conflict and natural disasters. Using a quantitative approach with panel data from the Central Statistics Agency (BPS), Bank Indonesia, and the Financial Services Authority (OJK), this study analyzes the relationship between population growth, per capita income, and poverty percentage through path analysis with the Sobel test. The results show that population growth has a negative and significant effect on per capita income, as well as a positive impact on increasing poverty. Meanwhile, per capita income is shown to have a negative and significant effect on poverty, indicating that an increase in income can reduce the poverty rate. Mediation analysis reveals that per capita income acts as a significant intervening variable, proving that population growth not only affects poverty directly, but also indirectly through a decrease in per capita income. These findings highlight the importance of policies that control population growth while promoting economic growth based on income generation to reduce poverty in Aceh. The policy implications of this study emphasize the need for integrated development programs, improved access to education and health, and strengthening productive sectors to strengthen the economic resilience of the community.